Coexistence in wireless networks : challenges and system-level solutions in the unlicensed bands - Golmie, Nada (Cambridge University Press, 2006)
The increasing popularity of wireless networks makes interference and cross-talk between multiple systems inevitable. This book describes techniques for quantifying this, and the effects on the performance of wireless networks operating in the unlicensed bands. It also presents a variety of system-level solutions, obviating the need for new hardware implementations. The book starts with basic concepts and wireless protocols before moving on to interference performance evaluation, interference modeling, coexistence solutions, and concluding with common misconceptions and pitfalls. The theory is illustrated by reference to real-world systems such as Bluetooth and WiFi. with a number of case studies and many illustrations, this book will be of interest to graduate students in electrical engineering and computer science, to practitioners designing new WLAN and WPAN systems or developing new techniques for interference supression, and to general users of merging wireless technologies.